Developing Islamic-Based Botanical Encyclopedia as a Learning Resource - Nurutstsany, Elfrida; Hidayat, Saifullah; Hayati, Nur (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2020)
Learning resources need to be developed based on current developments. The purpose of this research was to develop an Islamic-based Botanical Encyclopedia and test its quality. The method used to develop the encyclopedia was Research and Development (R&D) with the 4D model (Design, Define, Develop, and Disseminate) proposed by Thiagarajan in 1974 as the development model. The research instrument had been validated by the material, media, and integration experts. The average percentage of the validation result was 88% (a very valid category). The small-scale trial obtained a percentage of 89% (very valid), and the large-scale trial obtained a percentage of 85% (very feasible category). The results indicated that the developed Islamic-based Botanical encyclopedia could be used as a resource for independent learning.